Policy recommendations for export promotion - Rajapatirana, Sarath (Estudios de Economía, 2016)
The paper examines policy recommendations for export promotion and accepts distortion-correction as the objective that fits well with received trade theory, policy experience and political economy considerations. Evaluating the new trade theory that has the objective of capturing a larger share of the global market, the paper notes is theoretical validity but limited value for policy recommendation. Support to specific export activities can be accommodated within a framework of distortion-correction. But that support has to be at the initiative of the private sector, it should be subject to evaluation is an investment in knowledge, and time bound.